2018
DOI: 10.3389/fendo.2018.00135
|View full text |Cite
|
Sign up to set email alerts
|

Can a Proper T-Cell Development Occur in an Altered Thymic Epithelium? Lessons From EphB-Deficient Thymi

Abstract: For a long time, the effects of distinct Eph tyrosine kinase receptors and their ligands, ephrins on the structure, immunophenotype, and development of thymus and their main cell components, thymocytes (T) and thymic epithelial cells (TECs), have been studied. In recent years, the thymic phenotype of mutant mice deficient in several Ephs and ephrins B has been determined. Remarkably, thymic stroma in these animals exhibits important defects that appear early in ontogeny but little alterations in the proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 49 publications
(80 reference statements)
2
15
0
Order By: Relevance
“…In general terms, the evidence supports that proper TEC-thymocyte interactions are a requisite for an adequate functional education of thymocytes and for the generation of a proper TCR repertoire. However, we [ 98 ] and other authors [ 82 , 99 , 100 , 101 ] have observed studying different experimental models that thymuses showing profound epithelial alterations maintain normal proportions of thymocyte subsets, including positive and negative selected thymocytes, and Treg cells.…”
Section: The Condition Of Ephb-deficient Thymusesmentioning
confidence: 99%
See 4 more Smart Citations
“…In general terms, the evidence supports that proper TEC-thymocyte interactions are a requisite for an adequate functional education of thymocytes and for the generation of a proper TCR repertoire. However, we [ 98 ] and other authors [ 82 , 99 , 100 , 101 ] have observed studying different experimental models that thymuses showing profound epithelial alterations maintain normal proportions of thymocyte subsets, including positive and negative selected thymocytes, and Treg cells.…”
Section: The Condition Of Ephb-deficient Thymusesmentioning
confidence: 99%
“…EphB-deficient thymuses, although specific in their phenotypes, show some common features, such as hypocellularity, importantly altered epithelium but few changes in the proportions of thymocyte subsets. In addition, the mutant phenotype becomes evident early in the development but gradually increases in correlation with the establishment of TEC-thymocyte interactions [ 98 , 103 ].…”
Section: The Condition Of Ephb-deficient Thymusesmentioning
confidence: 99%
See 3 more Smart Citations